The effects of professional development on instructional strategies and the resulting influences on student learning for a physics curriculum - Cleavinger, Laurie (Kansas State University, 2009)
In this study, the professional development for a physics program called Visual Quantum Mechanics (VQM) was observed and analyzed. Four of the participants in a summer institute as Kansas State University (KSU) volunteered to be observed by the researcher as they implemented the program into their classrooms during the next academic year. Observations were used to determine the effectiveness of the instructional strategies that they used. The students’ perception of the laboratory sessions was evaluated and student understanding of the physics concepts also was determined. Qualitative and quantitative data analyses indicated that the professional development as presented and supported by the KSU team provided teachers with the information necessary to use the VQM program successfully with their students. However, only 30% of the teachers implemented the program during the following school year. Instructional strategies advocated by the VQM program included use of the hands-on equipment and computer simulations as well as discussion techniques. Observations revealed that students were more attentive during laboratory activities and less attentive during the discussions. Nevertheless, discussion proved to be a valuable component of this process. The researcher concluded that high quality professional development encouraged teaches to implement VQM in their classrooms. Although teachers did not always follow the instructional strategies advocated by the program, the inquiry-based hands-on activities and computer simulations kept students attentive. As a result, there was significant learning directly attributable to VQM for the students who participated in the study. Students who finished a complete learning cycle within the activities showed more significant learning than students who did not complete a learning cycle. Professional development can be designed to encourage teachers to implement new skills. For Visual Quantum Mechanics, emphasizing the importance of the whole class discussions, presenting the connections between the concepts and the science standards, and focusing on strategies for implementation will provide additional confidence to teachers as they implement the program in their classrooms.
Keywords: Professional development; Instructional strategies; Physics curriculum; Education, Curriculum and Instruction (0727); Education, Sciences (0714); Education, Secondary (0533)